(untitled) (Revista Latino-Americana de Enfermagem, 2007)
This study analyzed questions presented by nursing technicians and auxiliaries during medication preparation and administration. Data were collected through a form in which nurses who worked in the hospitalization unit of a general hospital in São Paulo, Brazil, were asked to take notes of any questions asked to them. Most of the 255 questions were related to medication dilution (103). Regarding the answers source, only 7.5% of answers were obtained from pharmaceutical professionals, 35.5% of the answers given by nurses was incorrect or partially correct, which can constitute a factor for medication administration errors. In addition, there are no pharmacists present in hospitalization units of Brazilian hospitals. These professionals could, jointly with nurses, facilitate medication orientation to nursing professionals during preparation and administration, as well as to patients themselves.